(untitled) (Indian Journal of Animal Production and Management, 2024)
Dairy farming plays a crucial role in achieving Sustainable Development Goals (SDGs) by contributing to various aspects of sustainability such as household income; increased direct consumption of healthy and nutritious food; women’s empowerment and gender equality. The dairy sector in India is dominated by cows and buffalos to produce milk and milk derivatives. However, rearing of Yak is commonly found in certain parts of India like Sikkim, Ladakh and Arunachal Pradesh nestled in lofty peaks of the Himalayas with rugged landscapes. In these climatic zones, yak herding communities have sustained themselves for centuries, preserving their rich cultural heritage. The yak herders have preserved their unique age-old practice of traditional yak rearing and Indigenous knowledge. In these states, the diminishing pastoral communities are engaged in the production of milk and milk derivatives such as fermented cheese and butter derived from yak. From the perspective of yak farming a smaller number of studies were conducted that too in Western countries. In the above context, the present study focuses on understanding the present scenario and prospects of yak herding relative to their current dairy products marketing and production models. The study also emphasizes the problems and opportunities in the field of yak herding in Northeast India, with special reference to Arunachal Pradesh.